Keynes' denial of conflict: Why The General Theory is a misleading guide to capitalism and stagnation - Thomas I. Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2023)
Keynes' General Theory was a massive step forward relative to classical economics, but it was also a step backward in its denial of the conflictual nature of capitalism. There is need to understand Keynes' technical contributions regarding the workings of monetary economies, but also need to understand the flaws within his thinking and the consequences thereof. Keynes made a fundamental contribution elucidating the mechanism of effective demand, and he also has claim to be the preeminent monetary theorist. However, owing to his denial of conflict, he had a flawed view of capitalism which is why establishment Keynesianism struggles to explain contemporary stagnation. That flawed view also undermines the case for Social Democracy. Contrary to conventional wisdom, his view of capitalism is supportive of Neoliberalism and Keynes can be viewed as a compassionate (Third Way) Neoliberal.
Keywords: B2; B22; B3; B31; E00; P1; 330; Keynes; The General Theory; conflict; capitalism; stagnation; bastard Keynesians